2012
DOI: 10.1111/j.1574-6968.2012.02506.x
|View full text |Cite
|
Sign up to set email alerts
|

Futile attempts to differentiate provide molecular evidence for individual differences within a population of cells during cellular reprogramming

Abstract: The heterogeneity of cell populations and the influence of stochastic noise might be important issues for the molecular analysis of cellular reprogramming at the system level. Here, we show that in Physarum polycephalum, the expression patterns of marker genes correlate with the fate decision of individual multinucleate plasmodial cells that had been exposed to a differentiation-inducing photostimulus. For several hours after stimulation, the expression kinetics of PI-3-kinase, piwi, and pumilio orthologs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(57 citation statements)
references
References 19 publications
5
52
0
Order By: Relevance
“…All these belong to the same hierarchy of ontologies, so all these can be summarized with the lower and more specific category, i.e., the ‘calcium ion binding’ GO term. Both analyses of GO annotations correlate well with previous studies that point to the upregulation of genes associated with the ion transport in the light-induced plasmodium 13,20…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…All these belong to the same hierarchy of ontologies, so all these can be summarized with the lower and more specific category, i.e., the ‘calcium ion binding’ GO term. Both analyses of GO annotations correlate well with previous studies that point to the upregulation of genes associated with the ion transport in the light-induced plasmodium 13,20…”
Section: Resultssupporting
confidence: 87%
“…In these works, both the assembly and mapping procedures were achieved using the mouse genome as a reference. Previously, we succeeded in measuring the expression on a set of 35 differentially regulated genes in populations of single-cells, using the GeXP RT-PCR platform 20. Here, using the power of RNA-seq to obtain whole transcriptomes without relying on previous genomic information, we were able to characterize a large set of expressed genes in different samples during the sporulation of Physarum , an organism without a known genomic sequence.…”
Section: Resultsmentioning
confidence: 99%
“…) as well as quantitative multiplex RT–PCR (GeXP) analyses with RNA samples prepared from individual plasmodial cells (Hoffmann et al . ) have shown that at 6 h after induction by a far‐red light pulse, that is, shortly downstream of the point of no return, the expression level of many genes has already changed drastically. Some genes are differentially regulated even at 2 h (Hoffmann et al .…”
Section: Resultsmentioning
confidence: 99%
“…Afterwards the RNA was precipitated with ethanol, and digested with rDNase to remove DNA contamination as described (Hoffmann et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…Systems-level biological modeling is a necessary and powerful tool for understanding how the regulatory network achieves a switch between the two stable states of a bistable behavior. Bistability is discussed with respect to all-or-none cellular processes such as differentiation, proliferation, survival and apoptosis [1][2][3][4][5][6]. However, much evidence about reversible switches has been observed in the regulatory network in biological experiments [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 97%